Model Kepemimpinan Kepala Sekolah Berbasis Hadis: Sintesis Konseptual Dan Empat Pilar Praktik - Aulia Silmi -; Mulyawan Safwandy Nugraha (JURNAL KAJIAN ISLAM MODERN, 2026)
ABSTRACT This study aims to formulate a hadith-based leadership model for school principals through a conceptual synthesis relevant to the challenges of contemporary Islamic education. The study employed a qualitative approach with literature study methods and thematic analysis of hadiths on leadership and education sourced from the books of Sahih al-Bukhari, Sahih Muslim, Sunan Abu Dawud, and Sunan Ibn Majah. The criteria for the selected hadiths were authentic and relevant to leadership and education. Data analysis was carried out through thematic coding and conceptual mapping. Furthermore, data validation was carried out using the triangulation method of interpretation between classical ulama's discourses and contemporary leadership theories. The results show that the Prophet's hadiths contain fundamental leadership values ​​that can be mapped into four main pillars, namely spiritual (piety and trustworthiness), ethical (justice and exemplary behavior), professional (competence and accountability), and social (service and participation). These four pillars are highly relevant to contemporary leadership models such as spiritual leadership, transformational leadership, instructional leadership, and servant leadership. The contribution of this research lies in strengthening the conceptual foundation of Islamic educational leadership based on the Prophet's hadith and offering an applicable framework in the managerial practices of school principals. Keywords: Islamic educational Leadership, Hadith Studies, School Principal Leadership, Spiritual Leadership